Recovery from workplace-induced airway inflammation 1 year after cessation of exposure. Issue 10 (25th July 2012) - Sikkeland, Liv Ingunn Bjoner; Eduard, Wijnand; Skogstad, Marit; Alexis, Neil E; Kongerud, Johny
Abstract : Background: Bacterial single-cell protein (BSCP) constitutes of dried bacterial mass which is used as protein enrichment in animal and fish feed. In the production of BSCP, workers are exposed to organic dust containing high levels of endotoxins (arithmetic mean 390 EU/m 3 in the moderate exposure and 5800–11 000 EU/m 3 in the high exposure groups) and have elevated levels of sputum neutrophils and cytokines associated with exposure. Objective: The aim of the present study was to investigate if airway inflammation among the workers had declined 1 year after cessation of exposure. Methods: Twenty-four non-smoking production workers (age 28–52) with a work history of 2–7 years were included in the study. Measurements: Markers of airways inflammation and innate immune function (using flow cytometry) were assessed in an exposure period and 1 year after cessation of exposure. Results: Sputum neutrophil proportion and numbers were significantly decreased 1 year after cessation of exposure to BSCP (43% vs 71%, 186 vs 598 neutrophils/mg sputum; p<0.001) as were eNO (17 ppb vs 21 ppb (p=0.01) and interleukin-1β (p<0.05) and interleukin-8 (p<0.05). Neutrophils had enhanced expression of CD11b/CR3 (p<0.01) and CD16/FcγRIII (p<0.001) and macrophages had lower expression of CD86 (p<0.01) 1 year after cessation of exposure. Conclusions: One year after closure of the plant airway neutrophils and exhaled NO levels resolved to lower levels and cell surface phenotypes associated with innate immune function recovered to higher levels, indicating that these changes were partly reversible among workers who were no longer exposed to endotoxins in a BSCP plant.